Use of Mycobacterial Culture for the Diagnosis of Smear Negative TB Cases Among New Outpatients at NIDCH, Dhaka (Bangladesh Journal of Medical Microbiology, 2010)
In this prospective study out of 300 randomly selected clinically and/or radiologically suspected TB patients ultimately data of 277 cases were analyzed. Among 23 excluded cases, 6 were positive by microscopy, 5 responded with broad spectrum antibiotics, and 12 were contaminated. After 2 months follow up with anti TB drugs, a total of 124 TB cases were diagnosed of which 121 (44%)were culture positive. Three cases were diagnosed by empirical anti TB treatment. A total of 153 cases were true negative by mycobacterial culture. Of 121 isolates 119 were typical and 2 were atypical mycobacteria. In this group, the sensitivity, specificity, positive predictive value and negative predictive value of mycobacterial culture were 97.63%, 100%, 100% and 98.1% respectively. Among the culture proven cases; 79% were prevalent in male and 21% in female. Case positivity was significantly higher among patient having symptoms of cough with hemophtysis with or without fever(58%) than the patients with constitutional symptoms. No advanced or cavitary lesions were seen on X-ray among culture proven cases. Majority culture proven cases(72%) had minimal lesion on X-ray. After two months anti TB therapy 119 culture proven cases and three culture negative cases improved clinically and radiologically.Bangladesh J Med Microbiol 2010; 03 (02): 23-26